Leptochilus sarawakensis nom. nov. (Polypodiaceae) from Malaysia - Zhang, Liang; Zhang, Li-Bing (Phytotaxa, 2018)
Recent molecular work has found that the fern genera Colysis C. Presl (1849: 146), Kontumia S.K. Wu & K.L. Phan (2005: 245), and Paraleptochilus Copeland (1947: 198) should be subsumed under Leptochilus Kaulfuss (1824: 147) (Dong et al. 2008, Kreier et al. 2008, Kim et al. 2012, Zhang et al. in press) so that Leptochilus can be maintained as monophyletic. The newly defined Leptochilus is then characterized by having an epiphytic habit, simple sterile leaves (except in Kontumia), and much contracted fertile leaves fully covered (except in Kontumia) with sori (acrostichoid sori). Following the results of a new molecular phylogeny (Zhang et al. in press) and morphological study nine new combinations in Leptochilus were made recently (Zhang et al. 2018) including L. fluviatilis (Lauterbach 1910: 507) Liang Zhang & Li Bing Zhang in Zhang et al. (2018: 173). However, the epithet “fluviatilis” is not available when Polypodium fluviatile Lauterbach in Winkler (1910: 507) is transferred to Leptochilus. Here we provide a new name for Polypodium fluviatile in Leptochilus.